The wizard - Martin, Bill, 1916-2004.; Schaefer, Alex, 1969- (San Diego : Harcourt Brace, 1994)
A wizard and his assistant cast a spell that ends up making the wizard disappear.
1.6
K-3
K-3
School Library Journal
Booklist
Kirkus Review
Keywords: Wizards -- Fiction; Magic -- Fiction; Stories in rhyme; Wizards -- Fiction; Magic -- Fiction; Stories in rhyme